ANALISA HUKUM DAMPAK HAK DAN KEWAJIBAN LEMBAGA PEMASYARAKATAN DITINJAU DARI UNDANG-UNDANG NO 22 TAHUN 2022 TENTANG PEMASYARAKATAN - Muhamad Rico Paura; Ardison Asri (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
This study analyzes the legal impact of overcapacity in correctional institutions (Lapas) on the implementation of Law No. 22 of 2022 concerning Corrections. Prison overcapacity is a serious problem that impacts various aspects, including inmates' rights, the quality of correctional facilities, and the effectiveness of their function as a place of correctional facilities and social recovery. This study will examine legally how prison overcapacity violates the basic principles of correctional facilities stipulated in Law No. 22 of 2022, identify the negative impacts it causes, and provide recommendations for solutions to address this problem.